The thermolysis of ruthenium(II, III) ammine complexes in water solutions at the increased temperatures and the solid phase. - E. V. Fesik; V. V. Grebnev; G. D. Malchikov (Тонкие химические технологии, 2008)
In this work reactions of the hexaammine ruthenium(II) - [Ru(NH3)6]Cl2 and “ruthenium red” -[Ru3O2(NH3)14]Cl6 • 4Н2О chlorides in the water alkaline solution at 190˚С (autoclave) and in the solid phase are investigated. The mechanism of restoration of the ruthenium ion by inside sphere ammonia up to the metal condition is offered.